2018
DOI: 10.1021/acsphotonics.7b01253
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Lasing Action in GaN Quantum Wells in the Infrared 1.5 μm Region

Abstract: Large-scale optoelectronics integration is strongly limited by the lack of efficient light sources, which could be integrated with the silicon complementary metal-oxide-semiconductor (CMOS) technology. Persistent efforts continue to achieve efficient light emission from silicon in the extending the silicon technology into fully integrated optoelectronic circuits. Here, we report the realization of room-temperature stimulated emission in the technologically crucial 1.5 µm wavelength range from Er-doped GaN mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…An adjustable shield was placed on the top of the sample to control the excitation length up to 1000 µm. [17] To achieve lasing operation, an optical cavity has been created from both polished edges of the sample. Two converging lenses with focal lengths of 10 and 24 cm were used to collect the edge-emission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An adjustable shield was placed on the top of the sample to control the excitation length up to 1000 µm. [17] To achieve lasing operation, an optical cavity has been created from both polished edges of the sample. Two converging lenses with focal lengths of 10 and 24 cm were used to collect the edge-emission.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the lasing threshold in the GaN:Er epilayer is a few times higher compared to those from Er-doped GaN nanolayers in multiple quantum well GaN/AlN structures. [17,39] In these structures, the multiple quantum wells provide an enhancement of the quantum efficiency for the infrared (1.5-m) emission band through the strain engineering, and carrier/exciton quantum confinement effect. [17,39] To explore the gain coefficient from the peaks of PL emission, we have used the well-known VSL method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Er-doped GaN multiple quantum wells samples were prepared by metal organic chemical vapor deposition (MOCVD) on a c-plane sapphire substrates and had excellent material qualities [13,14]. The X-ray diffraction and photoluminescence (PL) measurements indicated that GaN:Er epilayers have high crystallinity, without second phase formation, and exhibit a strong room-temperature emission at 1.5 µm with a low degree of thermal quenching [15].…”
Section: Samples and Experimental Resultsmentioning
confidence: 99%